Reconhecimento e certificação de saberes não formais na educação profissional de jovens e adultos : análise política da política - Urbano, Fernanda Santana de Souza (2013)
Current recomposition capitalism, driven by technological developments and located within the neoliberal has unleashed profound changes in work in the production and the social relations. These changes, is to reform education policy professional acting purpose form a new type of worker to meet the demands that need in the world of work, with better conditions of productivity in domestic market. This is a perspectival that combines knowledge acquired throughout living and working in brazil comes to make an institutional giving workers certification, delineating, from that, the subject of this dissertation and objective of the study. Analyze the politics of public recognition and certification of knowledge no formal (network CERTIFIC), implemented by federal institutes of education, science and technology in the period 2010 and 2012 in the context of capitalism contemporary transformations. Worry in understanding how the recognition of knowledge no formal and if different distance of paradigm of skills, so in fashion professional qualification in youth and adult in brazil, and, in the same way as a policy relates to the trend workfare in social policy. Policy analysis in search reveal the contradictions and determination, with bases and sources in documentary some research findings are. On the scope policy is restricted and had considered the period reduced number of workers with certificates, unveiling your reach limited. The criteria access and se constitutes with limited access. The criteria access and se constitutes with characteristics of exclusion because education requirement is incompatible with the public, and young adults in process are submitted for schooling and tend to abandonment of program. Professional education in Brazil have so not score perennial and financing sources, the same way network CERTIFIC, since this is a national action's aggregate efa. The own analysis of director of professional education spending in between the public and the private sector in the supply of goods and services, exposes the spraying of intense action as put another factor of obstacles effective public policy. The same way, not advanced participation and social control of public policies professionals. Register, avanço es in concept, for certification of knowledge no formal outlines a theoretical doing a counterpoint-political-cultural theory and methodology as models of skills, such linked by international organization, accentuating a proposed design diagnostic evaluation in training as part of an educational process dialogic, as if the standardization of distance professional profiles prepared without the participation of subjects that work, which indicates a process for reconstruction of professional career in your history, rescuing worker for the importance of their experience and professional certification which can come to represent for workers, the elimination of barriers to insert and progression as professional for continuation of studies. Also if this aspect of distance as workfare trend of social policy.